Treatment Patterns and Outcomes of Stable Hips in Infants With Ultrasonic Dysplasia. Issue 2 (15th January 2019) - Kim, Harry K. W.; Beckwith, Terri; De La Rocha, Adriana; Zepeda, Erica; Jo, Chan-Hee; Sucato, Dan
Abstract : Introduction: No clear practice guideline exists for the management of stable hip with ultrasonic dysplasia (UD). This study assessed the treatment patterns for stable UD and determined the outcomes of Pavlik harness (PH) treatment or observation (OB). Methods: This is a prospective study of 80 infants (107 hips) aged ⩽12 weeks at presentation diagnosed with stable UD. Results: Sixty-five hips were treated with PH, whereas 42 hips were observed. Patients who were older at the time of initial sonogram and those with lower head coverage were more likely to be treated with PH. The mean head coverage was lower in the PH group, indicating more severe UD. At a 2-year follow-up period, 93% of patients in the OB group and 87% in the PH group had a good radiographic outcome. Discussion: Head coverage and age at first sonogram had a significant influence on the treatment decision for PH. A milder ultrasonic hip dysplasia can be observed because 93% of the patients who were observed had a good outcome. Level of Evidence: Level II: prospective cohort study